Potential distribution of six endemic species of Stanhopea (Orchidaceae) genus in Mexico - Hernández de la Cruz, Mayra; Alanís-Méndez, José Luis; Chagoya-Fuentes, Jorge Luis; Enciso-Díaz, Oswaldo Javier (Current Botany, 2022)
Stanhopea is an orchid’s genus that includes 55 species distributed from Mexico to Argentina. However, due to its horticultural potential, a decrease in wild populations has been generated by the effect of over-collecting, further aggravated by the effect of habitat destruction, placing some species of Stanhopea from Mexico in some risk categories. In this work, the potential distribution areas of six endemic Stanhopea species in Mexico and in some Federal Natural Protected Area (ANP) were modeled with the use of the MaxEnt software. The potential distribution of the six endemic species in Mexico was obtained, in addition to the fact that it is possible to find one or more species within 74 ANPs.